If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-1=3x+2
We simplify the equation to the form, which is simple to understand
-1=3x+2
We move all terms containing x to the left and all other terms to the right.
-3x=+2+1
We simplify left and right side of the equation.
-3x=+3
We divide both sides of the equation by -03 to get x.
x=-1
| 9-18x+17-7x=26 | | 6x=4x-2 | | 6x-y=z | | -5(6y+6)=30 | | y=12.50x+100 | | 26=m/26+5 | | 7x-1=x+11 | | 3(2x-1)+5=5(x+1) | | 5x-14=x | | 2y+9=5(y+3) | | 2(2x-1)=5x+4-2 | | 1+2x=2(x-1) | | 5d+20=7d-4 | | 3x=6x+12 | | -40x=5 | | 4+6x=8x-2 | | 5*n=-15 | | 2x+3y-6(6x-8y)= | | 2[m-3]=m+5 | | 77=-6x+3x | | x^2-12x-44=0 | | 9x-17-12+3=-2 | | 8[a+2]=28-4a | | 25-4x-18-3x=-42 | | 10-[-d]=3 | | 5[x+3]=4x+5 | | X-12=3x+24 | | 3x+4=2x+2 | | 2n+1=o(n) | | -10+14g=14g | | (8x-3)-(4x+1)= | | (2x+3)(-4x+7)=0 |